Cardiometabolic risk profile in relation to the practice of healthy habits in a sample of Spanish workers - Pere Riutord Sbert; Bartomeu Riutord Fe; Neus Riutord Fe; Sebastiana Arroyo Bote; Ángel Arturo López González; José Ignacio Ramírez Manent (Archivos Latinoamericanos de Nutrición, 2021)
Insulin resistance is a pathological entity that can lead to alterations in lipid metabolism and can increase cardiovascular risk. Objective. The aim of this study was to assess the influence of different sociodemographic variables such as age, sex and social class and healthy habits such as smoking, physical activity and adherence to the Mediterranean diet on the cardiometabolic profile of Spanish workers. Material and methods. A descriptive, cross-sectional study was carried out in 1457 Spanish workers in an attempt to evaluate the effect of healthy habits (physical exercise determined with the IPAQ questionnaire, Mediterranean diet and tobacco consumption) and sociodemographic variables (age, sex and social class) on the values of different insulin resistance scales. Results. The progressive increase in the level of physical activity and high adherence to the Mediterranean diet achieved an improvement in the mean values and in the prevalence of elevated values in all the insulin resistance scales analyzed in this study. Age over 50 years and belonging to the least favored social classes (social classes II-III) were the variables that increased the risk of presenting insulin resistance. Male sex also increased the risk of presenting insulin resistance. Conclusions. The different healthy habits such as vigorous physical exercise and high adherence to the Mediterranean diet improve the values of the different scales that assess insulin resistance.